Perceptions of lymphoedema treatment in patients with breast cancer – a patient perspective. Issue 1 (9th April 2014) - Karlsson, Katarina; Biguet, Gabriele; Johansson, Karin; Nilsson‐Wikmar, Lena
<x xml:space="preserve">Abstract</x> Lymphoedema after breast cancer surgery is a chronic condition. Lymphoedema treatment consists of information/advice, compression, physical exercise, skin care, and manual lymph drainage. Little is known about how patients experience, adapt, and respond to lymphoedema treatment. Thus, the purpose of the study was to investigate and describe women's perceptions of lymphoedema treatment after breast cancer surgery. Sixteen women with breast‐cancer‐related lymphoedema, recruited from four hospitals and two rehabilitation clinics, participated in the study. Semi‐structured interviews were conducted and analysed using a phenomenographic method. Five qualitatively different categories of description could be identified: uncertainty, disappointment, guilt and shame, safety, and autonomy. The categories could be described based on a two‐dimensional structure: the patients role (internal vs. external locus of control) and an understanding of lymphoedema as a chronic disease or a burden. The study has provided a deeper understanding of different ways in which patients perceive and respond to lymphoedema treatment. The present findings enable the lymphoedema therapist to individualise treatment and counselling based on each patient's approach to the patient role, ability to take responsibility for treatment, and acceptance of lymphoedema as a chronic disease.